Análise in vitro da corrosão de braquetes revestidos por nitreto de titânio - Lenza, Eduardo Beaton (2006)
The metallic alloys used in the manufacture of orthodontic appliances when exposed to the oral environment are subjected to chemical, mechanical and physical alterations, which could lead to a corrosion process. The metallic ions released from this process may induce adverse effects in the organism leading to hypersensitivity and cytotoxicity reactions. With the purpose of decreasing or even eliminate the corrosion process, brackets coated with a thin layer of titanium nitride are being commercialized. The aim of this study was to compare the in vitro corrosion process of three types of brackets: stainless steel, manganese steel and manganese steel coated with titanium nitride from the commercial brand Morelli®, immersed in artificial saliva for 42, 63 and 84 days. After these time periods, the saliva extracts were removed and submitted to atomic absorption spectrophotometry to determine and quantify the metallic ions released. Surface alterations on the brackets were evaluated by scanning electron microscopy (SEM). The results of this study demonstrate that, in spite of the bracket alloy composition, all had undergone corrosion after 84-day period of immersion in artificial saliva. However, the stainless steel brackets presented more surface alterations indicative of corrosion sites than the other brackets. The greatest nickel ion concentration was detected in the stainless steel(3,60g/mL) bracket extracts after 84-day period of immersion in artificial saliva. Manganese steel brackets with or without titanium nitride coating showed to be less prone to corrosion than stainless steel brackets.